(untitled) (Journal of Atomic and Molecular Sciences, 2017)
We simulate the high order harmonic generation (HHG) in the frequency domain and attosecond pulse in the time domain from helium atom subjected to the polarization gating pulse composed of the two counter-rotation circularly polarized pulses with longer pulse duration by using the strong field approximation model. It is found that when the width of the polarization gate is adjusted from traditional half optical cycle to one optical cycle, the peak position of the synthesized pulse moves to inside the gate from outside the polarization gate due to the shortening of time delay between two pulse peaks. As a result, harmonic spectrum with the high efficiency and the regular plateau structure can be obtained, and further a single 127-as pulse can be generated from the polarization gating pulse with 10-fs pulse duration.